AB0786 Clinical results of swanson and avanta silastic implant arthroplasty of the metacarpophalangeal for the rheumatoid hand. (23rd January 2014) - Harada, R.; Nishida, K.; Hashizume, K.; Nakahara, R.; Saito, T.; Kanazawa, T.; Ozawa, M.; Machida, T.; Ozaki, T.
Abstract : Background: The arthroplasty of the metacarpophalangeal (MCP) for the rheumatoid hand was first described in 1940 by using vitallium prosthesis. After that, metallic hinge type, ball & socket type, surface replacement type and different type of prostheses are being developed, but none of these has been shown so far to be superior to the silastic implant, especially Swanson implant. Objectives: In the silastic implants, Swanson arthroplasty is referred to as the gold standard. The AVANTA silastic implant was also based on the concept of "piston effect" and "encapsulation" as the Swanson implant 1) . The purpose of this investigation was to compare the clinical outcome of Swanson and AVANTA silastic implant arthroplasty of the MCP joints for patients with rheumatoid arthritis. Methods: A total of 48 Swanson and 70 AVANTA implants were inserted in 38 hands of 34 patients (1 man, 33 women). The mean age of patients at the surgery was 61.9 ± 4.8 years in Swanson group and 61.0 ± 6.2 years in AVANTA group. The average follow-up period was 60.7 ± 20.5 and 21.3 ± 9.1 months in Swanson and AVANTA group, respectively. Pre- and post-operative clinical evaluations included active MCP extension and flexion, grip strength, pinch, ulnar deviation, osteolytic or sclerotic change in the radiograph, Health Assessment Questionnaire(HAQ), and Disabilities of the Arm, Shoulder and Hand(DASH) score. Statistical analysis were done using Mann-Whitney U test. Results: The mean postoperative active extension was -13.3° ± 16.2° in Swanson group, -10.7° ± 10.2° in AVANTA group (p=0.72), and flexion was 58.6° ± 19.8° in Swanson group, 59.3° ± 21.5° in AVANTA group (p=0.78). According to the Parkkila's criteria 2), the GradeII and more radiographic osteolysis was seen in 29% of Swanson group and 25% of AVANTA group. The GradeI and more radiographic sclerosis was seen in 73% of Swanson group and 69% of AVANTA group. The functional scores at the final follow-up were 1.4 ± 0.7 and 1.2 ± 0.8 (p=0.48) for HAQ-disability index and 54.9 ± 21.6 and 41.8 ± 21.6 (p=0.12) for DASH disability score in Swanson group and AVANTA group, respectively. There were three implant fractures in Swanson group. No patients had revision surgery during follow-up period. Conclusions: The AVANTA groups tend to obtain greater range of motion and better functional outcome, but there was not statistically significant difference between two groups. Implant fractures in the Swanson group might be associated with the silastic mechanical property and the longer follow-up period. References: Swanson, A.B. Flexible implant arthroplasty for arthritic finger joints: rationale, technique and results of treatment. J Bone Joint Surg 1972; 54A: 435-455 Parkkila TJ, Belt EA, Hakala M, et al. Grading of radiographic osteolytic changes after silastic metacarpophalangeal arthroplasty and a prospective trial of osteolysis following use of Swanson and Sutter prostheses. J Hand Surg Br 2005; 30(4): 382-387 Disclosure of Interest: None Declared